2012
DOI: 10.1080/01468030.2012.666818
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hybrid Optical Amplifiers for Dense Wavelength Division Multiplexed System with Reduced Spacings at Higher Bit Rates

Abstract: This article proposes various combinations of optical amplifiers for a dense wavelength division multiplexed system and investigates the impact of reduced channel spacing at high bit rates in terms of quality factor, bit error rate, eye closure, and output power. It is reported that the hybrid optical amplifier (Raman-erbiumdoped fiber amplifier [EDFA]) provides better results with a maximum covered single span distance (220 km) at channel spacing of 6.25 GHz. The maximum acceptable bit rate for the 12.5-GHz c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Simulation results have shown that the maximum acceptable bit rate for the 12.5GHz channel spacing DWDM system with the Raman-EDFA, Raman-EDFA-Raman, and EDFA-Raman-EDFA, need not to be greater than 20, 16, and 19Gbps, respectively [22]. analyzed.…”
Section: Parameters Valuementioning
confidence: 99%
See 2 more Smart Citations
“…Simulation results have shown that the maximum acceptable bit rate for the 12.5GHz channel spacing DWDM system with the Raman-EDFA, Raman-EDFA-Raman, and EDFA-Raman-EDFA, need not to be greater than 20, 16, and 19Gbps, respectively [22]. analyzed.…”
Section: Parameters Valuementioning
confidence: 99%
“…The simulated bit rate is at SONET/SDH rate (2.488Gbps) with a pseudorandom binary sequence. With respect to the overall power system performance, Raman-EDFA is found to have the best performance among the three types in the terms of quality factor, BER, and eye closure [22]. Shows the maximum single span distance of 220km which is achieved by Raman-EDFA amplifier at acceptable BER (4*10 10 ), quality factor (15.8 dB), and eye closure (2.23 dB) [22].…”
Section: Parameters Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Raman amplifiers can provide better results for L band amplification and better gain flattening because they can substantially reduce the impact of fiber nonlinearity [5]. Raman amplifiers have also been used for dense wavelength division multiplexed (DWDM) systems at high bit rates [6,7]. In [8,9] we have investigated the DWDM system at 10 Gbps data rate / channel.…”
Section: Introductionmentioning
confidence: 99%
“…Of the many nonlinear technologies investigated, semiconductor-based technologies are the most promising. SOA have been extensively investigated as basic building blocks because of their highly nonlinear characteristics and potential advantages of integration, compactness, reliability and cost effectiveness [5][6][7]. By using SOA as nonlinear medium, various all optical logic gates and complex circuits were proposed and also successfully implemented [8][9][10].…”
Section: Introductionmentioning
confidence: 99%